Involvement in practicing family planning among married men in kyaukpadaung township, mandalay region, myanmar - Zaw Myo Myint (2022)
In almost all land-bound areas over the world, men are assumed to be the most important individuals and care-givers of the family, but they are less cooperative in practicing their family planning especially regarding contraception use and antenatal care of their wives than in conducting other socio-economic activities. Traditionally, family planning has been mainly focused on women, and most of the methods are designed for women considering that it is the women who become pregnant and delivering reproductive health services as part of maternal and child health programs is convenient. The study aimed to investigate the proportion of male involvement in family planning and factors associated with male intention to be involved in family planning. Cross-sectional survey research was conducted among 388 married men, using systematic random sampling. The data were collected using questionnaire interviews during March and April 2019 and analyzed by frequency, percentage, Chi-square test, and multiple logistic regressions. The proportion of male involvement in families practicing family planning was 40.7%, condom being the most commonly used method. The factors influencing the practice of family planning included attitude towards family planning, subjective norm and intention to be involved. By following the Theory of Planned Behavior model, the variables such as attitude, subjective norm and intention were significantly associated with male involvement in family planning (P-value < 0.05). Respondents with positive attitudes were 2.12 times more likely to use family planning than those with negative attitudes. (ORAdj = 2.12, 95% confidence interval (CI) = 1.13-2.87, P-value 0.024). Regarding subjective norms, respondents with positive subjective norms were 2.11 times more likely to use family planning than those with negative subjective norms (ORAdj = 2.11, 95% CI = 1.25-3.25, P-value 0.011). Moreover, respondents who had good intention were 8.12 times more likely to use family planning than those with poor intention (ORAdj = 8.12, 95% CI = (4.71-13.82, P-value 0.001). The results suggested that effective education programs focusing on improving the knowledge of family planning, gaining a better attitude, complying with good subjective norms as well as reaching high perceived behavior control and good intention should be implemented to improve male involvement in practicing family planning.